Ten out of ten: a review of the last decade - Ken Arnold; Andrea Bandelli; Rachel Ellis; Jane Henderson; Michelle Henning; Rebecca Mellor; Theano Moussouri; Michal Nanoru; Hannah Redler-Hawes; Tim Snelson (Science Museum Group Journal)
In honour of the Journal’s tenth birthday, we asked a collection of authors with huge and varied experience of the cultural sector to think about the last decade and pick one thing that stands out for them. The brief was open and included books, exhibitions, digital innovation and general trends. The only restriction was that the contributions were short and were accompanied by a single image.